2017
DOI: 10.1007/s11356-017-0670-2
|View full text |Cite
|
Sign up to set email alerts
|

Immobilisation of metals in a contaminated soil with biochar-compost mixtures and inorganic additives: 2-year greenhouse and field experiments

Abstract: Besides carbon sequestration and improvement of soil properties, biochar (BC) has increasingly been studied as an amendment to immobilise heavy metals in contaminated soils. In a 2-year experiment, we analysed the effects of poplar BC (P-BC, mixed with compost) and gravel sludge with siderite-bearing material (GSFe) on a Cd-, Pb- and Zn-contaminated soil and on metal concentration in Miscanthus × giganteus shoots under greenhouse and field conditions. In the greenhouse, 1% (m/m) P-BC addition reduced NHNO-extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A similar trend was observed for the BAF of Ni and Zn, where combined application of ARN7 and GS-BC reduced the BAF irrespective of drought stress condition ( Figure 4 c,d). This might be as a result of the involvement of functional groups in the biochar in HM immobilization, chelation, or complex formation, resulting in decreased HM bioavailability and its uptake by plants [ 39 , 40 ]. Our results are in agreement with the findings of Naveed et al [ 33 ], who demonstrated that biochar amendment reduced Pb content in roots and shoots of Vigna radiata .…”
Section: Resultsmentioning
confidence: 99%
“…A similar trend was observed for the BAF of Ni and Zn, where combined application of ARN7 and GS-BC reduced the BAF irrespective of drought stress condition ( Figure 4 c,d). This might be as a result of the involvement of functional groups in the biochar in HM immobilization, chelation, or complex formation, resulting in decreased HM bioavailability and its uptake by plants [ 39 , 40 ]. Our results are in agreement with the findings of Naveed et al [ 33 ], who demonstrated that biochar amendment reduced Pb content in roots and shoots of Vigna radiata .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown to reduce cadmium discharge from the soil into nearby bodies of water (Ouyang et al 2017 ). Similarly, co-composting with biochar derived from woody biomass decreased zinc, lead, and cadmium concentrations in amended soils by 92, 86, and 5%, respectively (Karer et al 2018 ).…”
Section: Compostingmentioning
confidence: 99%